La forêt comme clôture : l’enfermement de l’habitat par la forêt - Claire Labrue (Projets de Paysage)
In the twentieth century, rural spaces such as the French middle mountains have been the scene of forestry reconquest and urban desertion, to the point that urban and forestry spaces are starting to interface and overlap. Glades, which have evolved from the socio-economic logic of the rural milieu, are the spatial translation of this dynamic. On the contrary to the traditional glade which is generated by forest clearing, the glade is currently the result of reforestification which is closing in the countryside. Living in a forested area is immemorial, but the lack of acculturation of the forest by the society which is becoming more urban reinforces the forest’s confining effect: the forest’s borders are causing environmental problems such as blocking views and shadows caused by the trees, the impact of which is influencing the feelings of the inhabitants. The forest is becoming therefore confining.